Um estudo para a avaliação da qualidade no trânsito em cidades brasileiras - Chiroli, Daiane Maria de Genaro (2011)
Due to the vertiginous technologic advance, the number of automobiles has been growing constantly in the whole world. In Brazil, considered to be the most economically influent and emergent country, this situation is increased by the country economic growth. Car selling has increased, so has the problems related to it, especially in less developed cities without a traffic program. These problems may vary in terms of security, flow, comfort, and others, what shows the importance of learning how it works and what influences it. This project presents a methodology used to aid the evaluation of Brazilian cities traffic called Quality Function Deployment (QFD), generally employed in the development of industrial products. The methodology allows the relation between technical variables and the user´s needs. Tests were developed using data from a city, and the results shows that this methodology may help to understand and manage the process.